Pengaruh Literasi Keuangan, Illusion of Control dan Overconfidence terhadap Keputusan Investasi pada Investor di Tulungagung - Nabila Amalia Karima; Nadia Roosmalita Sari (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze financial literacy, illusion of control and overconfidence on investment decisions for investors in Tulungagung. This research uses accidental sampling technique with a sample of 40 respondents from novice investors in Tulungagung. The results of this study indicate that the variables of financial literacy and overconfidence simultaneously affect investment decisions. Respondents belong to the group of investors who understand financial concepts well and feel confident. Meanwhile, the illusion of control variable has no effect on investment decisions. Respondents are included in the group of investors who are categorized as having higher financial literacy. The conclusion of this study is that financial literacy has a significant positive impact on investment among investors in Tulungagung. Keyword: illusion of control, investation, financial literacy, overconfidence